Knowledge, attitudes, and concerns about psilocybin and MDMA as novel therapies among U.S. healthcare professionals - Erin Wang; David S. Mathai; Natalie Gukasyan; Sandeep Nayak; Albert Garcia-Romeu (Scientific Reports, 2024)
Abstract Psychedelic-assisted therapy (PAT) with substances like psilocybin and MDMA has shown promise for conditions including depression and post-traumatic stress disorder. Psilocybin and MDMA may become approved medicines in the coming decade. This study assessed knowledge and attitudes regarding PAT among 879 U.S. healthcare professionals via anonymous online survey. Multivariable linear regression was used to identify predictors of openness to clinical use. Most participants (71.2%) were female and White (85.8%), with a mean (SD) age of 45.5 (12.7) years. Registered nurses (25.4%) and physicians (17.7%) comprised the largest professional groups. Respondents endorsed strong belief in therapeutic promise, and moderate openness to clinical use and support for legal access to both substances, with higher overall ratings for psilocybin compared to MDMA. Objective knowledge items revealed low knowledge of therapeutic uses, risks, and pharmacology. Primary concerns were lack of trained providers, financial cost, and potential contraindications. Prior psychedelic use, self-rated knowledge, younger age, and professional role predicted openness to clinical use of psilocybin and MDMA, with physicians reporting lower openness. As psychedelics continue to garner popular and scientific interest, results indicate a pressing need for additional formal training to provide balanced, evidence-based information from trusted sources.